Exploration and exploitation alliances in biotechnology: a system of new product development - Rothaermel, Frank T.; Deeds, David (Strategic Management Journal, 2004)
Abstract We link the exploration–exploitation framework of organizational learning to a technology venture's strategic alliances and argue that the causal relationship between the venture's alliances and its new product development depends on the type of the alliance. In particular, we propose a product development path beginning with exploration alliances predicting products in development, which in turn predict exploitation alliances, and that concludes with exploitation alliances leading to products on the market. Moreover, we argue that this integrated product development path is moderated negatively by firm size. As a technology venture grows, it tends to withdraw from this product development path to discover, develop, and commercialize promising projects through vertical integration. We test our model on a sample of 325 biotechnology firms that entered 2565 alliances over a 25‐year period. We find broad support for the hypothesized product development system and the moderating effect of firm size. Copyright © 2004 John Wiley & Sons, Ltd.